A second-generation micro/nano capsules of an endogenous primary un-metabolised bile acid, stabilized by Eudragit-alginate complex with antioxidant compounds - Armin Mooranian; Nassim Zamani; Momir Mikov; Svetlana Goločorbin-Kon; Goran Stojanovic; Frank Arfuso; Bozica Kovacevic; Hani Al-Salami (Elsevier, 2020)
Bile acids (BAs) are amphiphilic compounds and of recently have demonstrated wide range of formulation stabilizing effects. A recent study showed that primary un-metabolised bile acids (PUBAs) have β-cell protective effects, and synergistic antidiabetic effects when combined with antioxidant and anti-inflammatory drugs, such as probucol (PB). Thus, this study aimed to design and test microcapsules containing a PUBA incorporated with PB and an alginate-Eudragit matrix.Six types of microcapsules were developed without (control) or with (test) PUBA, and tested for internal and external features and β-cell protective effects.The incorporation of PB-alginate-Eudragit with PUBA produced stable microcapsules but did not exert consistent positive effects on cell viability in the hyperglycaemic state, which suggests that PUBA in alginate-Eudragit matrices did not exhibit synergistic effects with PB nor exerted antidiabetic effects. Keywords: Probucol, Microencapsulation, Eudragit, Alginate, Oral delivery, Diabetes mellitus